2015
DOI: 10.1152/ajpcell.00314.2014
|View full text |Cite
|
Sign up to set email alerts
|

Myotubes from lean and severely obese subjects with and without type 2 diabetes respond differently to an in vitro model of exercise

Abstract: Feng YZ, Nikolić N, Bakke SS, Kase ET, Guderud K, Hjelmesaeth J, Aas V, Rustan AC, Thoresen GH. Myotubes from lean and severely obese subjects with and without type 2 diabetes respond differently to an in vitro model of exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 58 publications
1
49
1
Order By: Relevance
“…[8] showed that lipid oxidation was increased in endurance trained men (athletes trained at a competitive level) compared to untrained men, as measured by lower respiratory exchange ratio. Increased lipid oxidation after exercise is also in line with observations from an in vitro model (electrical pulse stimulation) of myotube exercise [54, 55]. Bourlier et al .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…[8] showed that lipid oxidation was increased in endurance trained men (athletes trained at a competitive level) compared to untrained men, as measured by lower respiratory exchange ratio. Increased lipid oxidation after exercise is also in line with observations from an in vitro model (electrical pulse stimulation) of myotube exercise [54, 55]. Bourlier et al .…”
Section: Discussionsupporting
confidence: 80%
“…In pre-training myotubes we found increased oxidation and uptake of glucose and lower lipid accumulation in the overweight group compared to the normal weight group, as well as a possible association between lipid accumulation in vitro and insulin sensitivity in vivo . Several previous studies show no significant donor-related differences i basal glucose oxidation in myotubes [54, 5759], however Gaster [17] observed increased glucose oxidation in myotubes from obese patients with T2D compared to myotubes from lean donors. It was suggested that under certain conditions metabolism of myotubes from diabetic donors relies more on glucose oxidation than myotubes from lean donors [17].…”
Section: Discussionmentioning
confidence: 93%
“…; Feng et al . ) and our own preliminary experiments. Muscle glycogen content decreased by ∼20% (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…who reported that insulin‐stimulated glycogen synthesis did not change with EPS in primary myotubes from lean subjects and only improved in muscle from severely obese individuals (Feng et al . ). Explanations for this discrepancy may involve differences in the duration of the contraction (48 vs .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation